Relationship between tinnitus and olfactory dysfunction: audiovisual, olfactory, and medical examinations - Katayama, Naomi; Yoshida, Tadao; Nakashima, Tsutomu; Ito, Yasuki; Teranishi, Masaaki; Iwase, Takeshi; Sugiura, Saiko; Goto, Kensuke; Uchida, Yasue; Taki, Yosuke; Nakada, Takafumi; Tada, Ai; et al. (Frontiers in Public Health, 2023)
Introduction Sensory dysfunctions and cognitive impairments are related to each other. Although a relationship between tinnitus and subjective olfactory dysfunction has been reported, there have been no reports investigating the relationship between tinnitus and olfactory test results. Methods To investigate the relationship between tinnitus and olfactory test results, we conducted sensory tests, including hearing and visual examinations. The subjects included 510 community-dwelling individuals (295 women and 215 men) who attended a health checkup in Yakumo, Japan. The age of the subjects ranged from 40 to 91 years (mean ± standard deviation, 63.8 ± 9.9 years). The participants completed a self-reported questionnaire on subjective tinnitus, olfactory function, and hearing function, as well as their lifestyle. The health checkup included smell, hearing, vision, and blood examinations. Results After adjusting for age and sex, the presence of tinnitus was significantly associated with subjective olfactory dysfunction, poor olfactory test results, hearing deterioration, vertigo, and headache. Additionally, high serum calcium levels and a low albumin/globulin ratio were significantly associated with low physical activity and nutrition. Women scored higher than men in olfactory and hearing examinations, but there was no gender difference in vision examinations. Conclusion Subjective smell dysfunction and poor smell test results were significantly associated with tinnitus complaints. Hearing and vision were associated even after adjusting for age and sex. These findings suggest that evaluating the mutual relationships among sensory organs is important when evaluating the influence of sensory dysfunctions on cognitive function.